Saliva contamination effects at different application steps on bond strength of total etch two-step adhesive - Souza, Lidiane Costa de; Rodrigues, Nara Sousa; Aquino, Elizeu Ytalo Pereira; Melo, Mary Anne Sampaio; Cunha, Diana Araújo; Saboia, Vicente de Paulo Aragão (Journal of Health & Biological Sciences, 2019)
Introduction: there are clinical situations in the management of cavities favorable to saliva contamination. Human saliva is a complex mixture of oral fluids and it has been showed that the protein content of the saliva is responsible for the decrease in adhesive bond strength when contamination has occurred. Objective: this study aimed to evaluate the effect of saliva contamination during different steps of application of adhesive system on bond strength of total etch two-step adhesive system. Methods: twenty-five extracted human molars were ground flat to expose occlusal dentin. The bonding system and composite resins were applied to the dentin after etching step under five conditions (n=5/group): G1: control group–no contamination; G2: etching/ contamination/dry/adhesive system application; G3: etching/contamination/wash/dry/adhesive system application; G4: etching/adhesive system application/contamination/wash/dry/adhesive system re-application; and G5: etching/adhesive system application/contamination/dry. Microtensile bond strength was tested after specimens were stored in distilled water at 37ºC for 24h. Data (mean values -μTBS) were analyzed by ANOVA one-way and Tukey tests (α=5%), respectively. Results: groups G2, G3 and G4 revealed bond strength similar to the control (G1). Group G5 showed significantly lower bond strengths than other groups (p<0.001). Conclusion: the total- etch two-step adhesive tolerated salivary contamination except when the contamination occurred after application of the bond and it was only removed with an air jet and adhesive system was not reapplied.